Phosphazene-promoted anionic polymerization - Zhao, J.; Hadjichristidis, N.; Gnanou, Y. (Polimery, 2014)
In the recent surge of metal-free polymerization techniques, phosphazene bases have shown their remarkable potential as organic promoters/catalysts for the anionic polymerization of various types of monomers. By complexation with the counterion (e.g. proton or lithium cation), phosphazene base significantly improve the nucleophilicity of the initiator/chain-end resulting in rapid and usually controlled anionic/quasi-anionic polymerization. In this review, we will introduce the general mechanism, i.e. in situ activation (of initiating sites) and polymerization, and summarize the applications of such a mechanism on macromolecular engineering toward functionalized polymers, block copolymers and complex macromolecular architectures.